(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article examines international research on introducing preschool children to various professions and careers. Early career awareness plays a crucial role in children’s cognitive development, social understanding, and future educational choices. The study analyzes contemporary approaches, methodologies, and findings from research conducted in different countries regarding career education for children aged 3-7 years. The review encompasses diverse pedagogical strategies including role-play activities, virtual excursions, interactive games, and direct interactions with professionals. Research indicates that early exposure to professions helps children develop realistic career aspirations, reduces gender stereotypes, broadens their understanding of the working world, and enhances social-emotional competencies. The article discusses effective practices from various educational systems, challenges in implementing career education programs, and recommendations for educators and policymakers. Findings suggest that systematic, age-appropriate career education integrated into preschool curriculum significantly contributes to children’s holistic development and lays the foundation for informed future career decisions.